Approaches to minimize the effects of P‐glycoprotein in drug transport: A review. Issue 4 (1st February 2022) - Husain, Athar; Makadia, Vishal; Valicherla, Guru R.; Riyazuddin, Mohammed; Gayen, Jiaur R.
Abstract: P‐glycoprotein (P‐gp) is a transporter protein that is come under the ATP binding cassette family of proteins. It is situated on the surface of the intestine epithelium, where P‐gp substrate binds to the transporter and is pumped into the intestine lumen by the ATP‐driven energy‐dependent process. In this review, we summarize the role of the P‐gp efflux transporter situated on the intestine, the clinical importance of P‐gp related drug interactions, and approaches to minimize the effect of P‐gp in drug transport. This review also focuses on the impact of P‐gp on the bioavailability of the orally administered drug. Many drug's oral bioavailabilities can improve by concomitant use of P‐gp inhibitors. Multidrug resistance are reduced by using some naturally occurring compounds obtained from plants and several synthetic P‐gp inhibitors. Formulation strategies, one of the most important approaches to mimic the P‐gp transporter's action, finally enhancing the oral bioavailability of the drug by inhibiting its P‐gp efflux. Vitamin E TPGS, Gelucire 44/14 and other pharmaceutical/formulation excipients inhibit the P‐gp efflux. A prodrug approach might be a useful strategy to overcome drug resistance. Prodrug helps to enhance the solubility or alter the pharmacokinetic properties but does not diminish the pharmacological action. Abstract :